Convergent evolution of plant and animal embryo defenses by hyperstable non-digestible storage proteins - Pasquevich, María Yanina (2017)
Fil: Pasquevich, María Yanina. Universidad Nacional de La Plata. Instituto de Investigaciones Bioquímicas de La Plata; Argentina